Corporate debt, hybrid securities and the effective tax rate - Paolo M. Panteghini (Center for Economic Studies and ifo Institute (CESifo), 2008)
In this article we use contingent-claim analysis to calculate the effective tax rate (ETR) under corporate debt finance. In particular, we deal with both pure debt and two of the most well-known hybrid securities, i.e., convertible, and reverse convertible bonds. We show that: 1) effective taxation crucially depends on the characteristics of debt, and 2) existing measures of ETR can be dramatically biased, since they do not account for debt maturity, default risk or the ability to convert debt into equity.
Keywords: H2; 330; Capital structure; contingent claims; corporate taxation; hybrid securities; Fremdkapital; Wandelanleihe; Kapitalstruktur; Unternehmensbesteuerung; Steuerbelastung; Steuerinzidenz; Optionspreistheorie; Theorie